Some aspects of RF discharge in the "U-3M" torsatron - Berezhniy, V.L.; Ocheretenko, V.L.; Pavlichenko, O.S.; Pinos, I.B.; Prokopenko, A.V.; Tsybenko, S.A.; Lozin, A.V. (Вопросы атомной науки и техники, 2007)
Studies were made into the behavior of frequencies and harmonic power of the RF field used for plasma production and heating in the “U-3M” torsatron. Визначена динаміка зміни частот і потужності гармонік ВЧ-поля, яке використовується для створення і нагрівання плазми в торсатроні "У-3М". Определена динамика изменения частот и мощности гармоник ВЧ-поля, используемого для создания и нагрева плазмы в торсатроне "У-3М".